The predictive role of monocyte-lymphocyte ratio and plateletlymphocyte ratio in postmenopausal osteoporosis - Ibrahim Kale (Digital ProScholar Media, 2021)
Objective. To investigate the relationship between neutrophil to lymphocyte ratio (NEU/LY), monocyte to lymphocyte ratio (MO/LY), platelet to lymphocyte ratio (PLT/LY), mean platelet volume to lymphocyte ratio (MPV/LY), mean platelet volume to platelet ratio (MPV/PLT), plateletcrit to platelet ratio (PCT/PLT) and postmenopausal osteoporosis. Materials and Methods. The data of the patients who were admitted to Ümraniye Training and Research Hospital between January 2017 and July 2020 and had both bone mineral densitometry and hemogram tests on the same day were retrospectively scanned. A number of 177 patients who had been in natural menopause for at least one year and did not have any chronic disease nor used any medication were first divided into 3 groups: a number of 48 patients with osteoporosis, 103 with osteopenia and 26 patients included in the control group. Later on, 177 patients were divided into two groups: 151 patients with low bone mineral density and 26 patients were included in the control group. Results. There was no difference between the three groups in terms of NEU/LY, MPV/LY, MPV/PLT and PCT/PLT. The MO/LY ratio and PLT/LY ratio were statistically significantly higher in the osteoporosis group (p = 0.002, p <0.001, respectively). The MO/LY ratio was significantly higher in the group with low bone mineral density compared to the control group (p = 0.011), while there was no statistical difference between the two groups in terms of PLT/LY ratio (p = 0.281). Conclusions. This study shows that MO/LY and PLT/LY are quite simple and cheap markers that can be used in the diagnosis of postmenopausal osteoporosis and MO/LY in the diagnosis of postmenopausal low bone mineral density.